Economic evaluation of prostate cancer screening: a systematic review. (February 2015) - Lao, Chunhuan; Brown, Charis; Rouse, Paul; Edlin, Richard; Lawrenson, Ross
ABSTRACT : This review, based on published papers, aims to describe the costs of prostate cancer screening and to examine whether prostate cancer screening is cost effective. The estimated cost per cancer detected ranged from €1299 in The Netherlands to US$44, 355 in the USA. The estimated cost per life-year saved ranged from US$3000 to US$729, 000, while the cost per quality-adjusted life year (QALY) was AU$291, 817 and Can$371, 100. The most appropriate data for economic evaluation of prostate cancer screening should be the cost per QALY gained. The estimated costs per QALY gained by prostate cancer screening were significantly higher than the cost–effectiveness threshold, suggesting that even when based on favorable randomized controlled trials in younger age groups, prostate cancer screening is still not cost effective.